1994
DOI: 10.1007/bf02752218
|View full text |Cite
|
Sign up to set email alerts
|

Phenol block in the management of spastic cerebral palsy

Abstract: In the present series 116 cases of spastic cerebral palsy were selected; in whom perineal care and ambulation was affected. These cases were given peripheral nerve block (obturator 110, posterior tibial 134 and median nerve 2) with 6% aqueous phenol solution. The block relieved the spastic condition, allowed better nursing care, freed the patient from the embarrassment of a contorted limb, allowed voluntary movement to take place and eased in fitment of caliper to aid further ambulation. The period of effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 12 publications
0
12
0
2
Order By: Relevance
“…reported an average period of effectiveness to be 13 months (range 3-18 months) with 6% phenol in 115 cases of cerebral palsy. [9] None of the studies have evaluated the effect of obturator neurolysis over spasm frequency in the internal rotators of hip, which decreased significantly in our study. The spasms disturb the function of sitting at early stages of rehabilitation and walking.…”
Section: Discussionmentioning
confidence: 76%
“…reported an average period of effectiveness to be 13 months (range 3-18 months) with 6% phenol in 115 cases of cerebral palsy. [9] None of the studies have evaluated the effect of obturator neurolysis over spasm frequency in the internal rotators of hip, which decreased significantly in our study. The spasms disturb the function of sitting at early stages of rehabilitation and walking.…”
Section: Discussionmentioning
confidence: 76%
“…20,[28][29][30][31] Phenol use in children and adults with spasticity is primarily directed toward nerves that have a minimal sensory component and are easily localizable. Successful results have been reported in patients with multiple etiologies, including multiple sclerosis, stroke, torticollis, brain injury, and cerebral palsy.…”
Section: Indicationsmentioning
confidence: 99%
“…Clinical Experience Botulinum A toxin has been used in cerebral palsy (1) to diminish painful paravertebral spasticity,9 (2) to facilitate positioning and hygiene,9 (3) to improve ambulation, 8-1O,12-14,43 (4) as an alternative to serial casting,&dquo; (5) as a diagnostic aid to determine the efficacy of surgery,' (6) to augment or reduce therapy,44 (7) to facilitate or replace bracing,44 (8) to delay surgery,44 and (9) to improve upper extremity function. 15 Studies have demonstrated that botulinum A toxin injected intramuscularly without anesthesia is practical in a clinical setting8-1O,12 and appears to alter favorably the natural history of patients with dynamic foot deformity.…”
Section: Botulinum a Toxinmentioning
confidence: 99%
“…The use of botulinum A toxin is inappropriate or inadvisable (1) in the management of fixed contracture, (2) in the presence of certain specific neuromuscular diseases (eg, myasthenia gravis), (3) while a patient is actively being treated with medications that may exaggerate the response to neuromuscular blocking agents (eg, aminoglycoside antibiotics), (4) in muscle(s) that did not respond to alcohol or phenol injections, (5) in the presence of antibodies to botulinum A toxin, and/or (6) in the absence of objective benefit. SUMMARY Neuromuscular blocking agents have an important adjunctive role in the evaluation and nonoperative management of patients with S28 cerebral palsy.…”
Section: Contraindicationsmentioning
confidence: 99%